ACCOUNTING PERSPECTIVE ON THE ISLAMIC-DRIVEN ACCOUNTABILITY IN A TRADITIONAL ISLAMIC ORGANISATION IN JAVA - Prasetio, Januar Eko; Triyuwono, Iwan; Sukoharsono, Eko Ganis; Purwanti, Lilik (The International Journal of Accounting and Business Society, 2021)
Purpose —  This study explores an accounting perspective on the Islamic-driven accountability in Gus Miek’s Jantiko Mantab community, a traditional Islamic organization in Java. The Jantiko Mantab is an East Java-based community initiated by KH. Hamim Tohari Jazuli (Gus Miek) in 1970s. Regardless of the unique and controversial method of Gus Miek, this community was selected as the object due to its progressive development in the Islamic movement on the number of followers especially in grass root and marginalized communities in Java. The study focuses on two main public activities of the Jantiko Mantab, which are continuously held from one place to other places, namely Al Quran recitation (Semaan) and praising Allah using holy sentences (Dzikrul Ghofilin) in the congregation.Design/methodology/approach —  This study is qualitative research with a spiritual paradigm approach and uses a spiritual perspective analysis method through tawasul, zikir, and syir (pray). The study is conducted through bibliography reviews, interviews, and direct observations.Findings —  The results of this study showed Religious activities within the community were experienced to gain a comprehensive understanding of the founder, leader, and member perspectives on the organization’s accountability. Accountability in Jantiko Mantab was understood as a formal aspect of accounting, such as financial reports, and also performed and nurtured in accordance to the human task as Khalifatullah fil Ardh. The concept of Khalifatullah fil Ardh is embedded in their community and considered as the accountability uniqueness of Jantiko Mantab.Practical implications — Semaan Al-Qur’an and Dzikrul Ghofilin of Jantiko Mantab should make a change in interpreting the concept of accountability that is currently loaded with capitalist interests by incorporating Islamic values sourced from Al Qur'an and hadiths.Originality/value — This Islamic value, which is also delivered and reflected by their leaders, is likely to drive the member perception of the organization's accountability. Keywords —  Accountability, Islamic value, Islamic organization, Indonesia. Paper type — Case Study